Neurophysiological Commonalities and Differences Across Obsessive- Compulsive, Panic, Phobic and Generalized Anxiety Disorders - Montserrat Gerez; Enrique Suárez; Carlos Serrano; Lauro Castanedo; Armando Tello (Advanced Concepts in Medicine and Medical Research Vol. 9, 2023)
Disorders characterized by anxiety (AD) have been among the leading causes of global health-related burden for over 30 years. Prevalence has increased despite strong evidence of effective therapeutic interventions in transversal group studies, partly because of a high rate of recurrences and decreased responses in long-term individual histories. Comorbidity and pharmacological response among obsessive-compulsive (OCD), agora, social, and specific phobias (SD), panic (PD) and generalized anxiety (GAD) disorders suggest a single dimension: serotonin-dysfunction. Yet, psychiatric classifications conceptualize those entities as distinct, with strong support from various neuroscience fields. Understanding and targeting physiopathogenic mechanisms may improve the long-term therapeutic response, particularly when social, psychological, and biological factors are combined in most affected subjects, loading differently across individuals, but somewhat clustering by nosological entities. The primary purpose of this chapter is to examine for neurophysiological dysfunctions shared by, or different among PD, SAD, OCD and GAD. A sample population of 192 unmedicated patients and 30 aged-matched controls partook in this study. Ten independent factors have included in Hypothesis- related neurophysiological variables. Contingency tables and correspondence analysis75 with chi-square tests were used to describe the sample distribution and relation to clinical groups of the three categorical factors: EPI, cROI and side (Fig. 1; Table 3), Fisher linear discrimination for the quantitative ones The nonparametric analysis correctly classified 81% of the sample. Dysrhythmic patterns, decreased delta, and increased beta differentiated AD from controls. Shorter ERP latencies were found in several individual patients, mostly from the OCD group. Hyperactivities were found at the right front orbital-striatal network in OCD and at the panic circuit in PD. Our findings support diffuse cortical instability in AD in general, with individual differences in information processing deficits and regional hyperactivities in OCD and PD. This study findings suggest that neurophysiology can be used to identify ongoing dysfunctions, their relative weights and their interactive patterns on a moment-to-moment basis.